Analisis Pengaruh Attraction, Accessibility, Amenity, Ancillary terhadap Minat Berkunjung Wisatawan melalui Loyalitas Wisatawan sebagai Variabel Mediasi - Elinda Anandar Ningtiyas; Stella Alvianna (Media Wisata, 2021)
Indonesia has many tourist destinations that have great potential, one of which is artificial tourism. One of the tourist destinations visited by many tourists in East Java, namely Malang, is better known in all circles. This study describes the influence of tourism components consisting of Attraction, Accessibility, Amenities, Ancillary on Tourist Visiting Interest San Terra De Laponte Malang Regency through Tourist Loyalty as a mediating variable. This population is tourists who have visited the San Terra De Laponte destination with a sample of 65 respondents. Data analysis used multiple linear regression and hypothesis testing. From the analysis and discussion, it is found that Attraction, Accessibility, Amenities, Ancillary have a positive and significant effect on Tourist Loyalty. Furthermore, Attraction, Accessibility, Amenities, Ancillary have a positive and significant effect on Visiting Interest. This shows that what tourists get and what tourists feel have a positive impact so that they attract tourists to revisit San Terra De Laponte, Pujon, Malang Regency